Challenges to the Disciplines Contexts for the Liberal Arts. - Office of Education (DHEW), Washington, DC.; Office of Education (DHEW), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This conference report begins with a statement of purpose and an outline of organization for the conference. Three topics--human development, studies for all men, and teachers and teaching--were related to the liberal arts, the humanities, and the disciplines and were to be brought to focus by three synthesizing reports after the completion of the conference. Of the two reports included here, John Zell's deals with the anxiety involved in change despite its desirability in humanizing the humanities. Paul Olsen deals with the act of teaching and its translation by purposeful action into a humanizing action; it speaks specifically of insights gained during a student strike over Cambodia. Reactions to both the content and the organization of the conference from the resource people in attendance completes the critical content of the report. Participant's names and daily schedules are appended. (JH)
ERIC Note: Report of a TTT Cluster Workshop, Miami, Florida, June 21-22, 1970.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Conference Reports; Higher Education; Humanities; Humanities Instruction; Humanization; Intellectual Disciplines; Liberal Arts; Teacher Education; Teacher Educators; Teacher Workshops; Training Teacher Trainers Project